The blood-retinal barrier: leucine transport by the retinal pigment epithelium - Sellner, PA (J Neurosci, 1986)
The transport of leucine across the isolated bullfrog pigment epithelium-choroid was studied in a modified Ussing chamber. With the same concentration of leucine on both sides of the tissue, there was a net flux in the apical-to-basal (retina-to-choroid) direction. The concentration dependence of the apical-to-basal flux comprised at least 2 components: a carrier-mediated flux, with an apparent Km of 0.76 mM and a Vmax of 298 nmol/cm2/hr, and a linear component with a slope of 33.4 cm/hr. The basal-to-apical flux was linear to 10 mM leucine, with a slope of 60 cm/hr. In the absence of Na+, the apical-to-basal flux was inhibited 20%, while the basal-to-apical flux was unaffected. The apical-to-basal flux could be inhibited to the level of the basal-to- apical flux by removing glucose from the solution and adding KCN. Otherwise both fluxes were relatively unaltered by metabolic poisons. There appear to be 3 contributors to the apical-to-basal flux: a weakly Na+-dependent carrier, a linear component (diffusion), and a countertransport mechanism. The basal-to-apical flux must have 2 linear mechanisms, diffusion to the same extent as the opposite flux, and possibly pinocytosis.